Penerapan Sanksi Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Berdasarkan Undang-undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik di Pengadilan Negeri Medan (Studi Kasus Perkara Nomor 248/Pid.Sus/2016/PN.Mdn) - Saragih, Nessia Gresyola; Deliana, Evi; , Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The criminal defamation is a crime caused by the advancement of computer technology. Defamation is a lawless act that attacks the honor or reputation of others. The application of law against defamation offenders is regulated in Law Number 11 Year 2008 on Information and Electronic Transaction Article 45 paragraph (1): "Any person who meets the elements as referred to in Article 27 paragraph (1), paragraph (2), paragraph (3), or paragraph (4) shall be punished with a maximum imprisonment of 6 (six) years and/or a fine of not more than Rp 1,000,000,000.00 (one billion rupiah).The type of research or approach done by the author is the study of socio-legal law. This research conducted in Medan District Court. This location was chosen because of a criminal defamation case in Medan. In this study the authors use data sources that can be grouped as follows: Primary data, is data obtained directly in the location of research. Secondary data, is data obtained indirectly through the literature (library research).Article 27 paragraph (3) of Law Number 11 Year 2008 on Information and Electronic Transactions "any person intentionally and without right to distribute and/or transmit and/or make accessible electronic information and/or electronic documents containing insult and/or defamation. In the application of criminal sanctions against defamation cases in Number 4248/Pid.Sus/PN.Mdn, The Judge has sentenced the defendant Angelica Rivera to 2 (two) months imprisonment and stipulates that the crime is unnecessary, except later on the order of the Judge. The defendant was sentenced to a previous trial for 4 (four) months. The application of sanctions also concerns the judges' considerations that can alleviate punishment against defamation offenders.Keywords : Criminal act-Defamation-Social Media